Chronic lymphocytic leukemia in a child: A challenging diagnosis in pediatric oncology practice. Issue 5 (19th November 2013) - Demir, Hacı Ahmet; Bayhan, Turan; Üner, Ayşegül; Kurtulan, Olcay; Karakuş, Esra; Emir, Suna; Özyörük, Derya; Ceylaner, Serdar
<x xml:space="preserve">Abstract</x> Chronic lymphocytic leukemia/lymphoma (CLL) is an extremely rare disease during childhood. We report a 16‐year‐old female who presented with lymphadenopathies and she was diagnosed as T cell lymphoblastic lymphoma. Her chemotherapy response was minimal and clinical findings were unusual. Therefore, her biopsy specimen was re‐examined and diagnosis was changed to CLL. Chemotherapy protocol including fludarabine, cyclophosphamide, rituximab was administrated and good response was observed. In our patient deletion at 1q21.2 region that includes aryl hydrocarbon receptor nuclear translocator (ARNT) gene was detected via comparative genomic hybridization method. ARNT gene deletion may be a new mutation in chronic lymphocytic leukemia development. Pediatr Blood Cancer 2014;61:933–935. © 2013 Wiley Periodicals, Inc.